Interleukin 37 promotes angiogenesis through TGF-β signaling - Mengmeng Zhao (Nature Portfolio, 2017)
Abstract IL-37 is a novel pro-angiogenic cytokine that potently promotes endothelial cell activation and pathological angiogenesis in our previous study, but the mechanisms behind the pro-angiogenic effect of IL-37 are less well understood. Extending our observations, we found that TGF-β interacts with IL-37, and potently enhances the binding affinity of IL-37 to the ALK1 receptor complex, thus allowing IL-37 to signal through ALK1 to activate pro-angiogenic responses. We further show that TGF-β and ALK1 are required in IL-37 induced pro-angiogenic response in ECs and in the mouse model of Matrigel plug and oxygen-induced retinopathy. The result suggests that IL-37 induces pro-angiogenic responses through TGF-β, which may act as the bridging molecule that mediates IL-37 binding to the TGF-β receptor complex.